(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Cerebral vein and venous sinus thrombosis is a rare disease, accounting for less than 1% of all stroke cases. The most common and often the earliest symptom of cerebral vein and sinus thrombosis is headache. The diagnosis of the disease is significantly complicated by the lack of specific characteristics of this pain and the possible absence of other neurological manifestations. In this regard, headache is often the only complaint of patients with cerebral venous sinus thrombosis. Due to the variability of clinical symptoms, often subacute or slow development, the disease is diagnosed late or remains unrecognized at all. The most common thrombosis is the superior sagittal, lateral and transverse sinuses. In 2/3 of cases, thrombosis of several cerebral veins is observed. This paper presents the anatomical features of the structure of the venous system of the brain, issues of etiology, pathogenesis, clinical picture, diagnosis and treatment of cerebral vein and venous sinus thrombosis. The case histories of three patients who were treated at different times in the second neurological department of the Scientific Center of Neurology with a diagnosis of “cerebral sinus thrombosis” are presented, demonstrating modern possibilities for the diagnosis and treatment of venous circulation disorders.